MENINGKATKAN PEMAHAMAN SISWA PADA MATERI KEGIATANPERDAGANGAN INTERNASIONAL MELALUI MODEL JIGSAW TIM AHLI SISWA KELAS XI IPS 1MAN 2 JEMBER - Na'im, Hadi (Jurnal Pengembangan Pendidikan, 2013)
Abstract. Each learningactivities undertaken by teachers and students have a goal to achieve a passinggrade. In the school year 2010/2011 students who have not achieved masterylearning reaches 40%. Ideally in learning activities in the classroom masterylearning are achieved by 80%. Therefore, classroom action research wasconducted through two cycles, each cycle consisting of a plan stages, action inthe form of distribution activities and discussion groups, then performedobservations and the results will be a reflection for the next cycle. Jigsaw 'steam of experts model can improve students' understanding on the matter ofinternational trade. This is indicated by the teacher performance appraisal of62.5%, the average student value of 83.33%. In the second cycle the value ofteachers' performance by 93.75% with an average value of 93.75%. The testresults of students in the first cycle by an average of 68.06 and at 80.56 onthe second cycle. Researchers recommend to other researchers to develop a modelof instructional strategies Jigsaw 's team of experts to be combined with otherlearning approaches. Kata kunci : understanding of the material, the modeljigsaw expert team